ESTUDO DO SINERGISMO DE ANTIOXIDANTES NATURAIS PARA BIODIESEL - Boschen, Nayara Lais (2019)
Nowadays, the use of fossil fuels as an energy source is seen as an environmental villain. Biodiesel came as a bioenergetics solution to the use of diesel, minimizing environmental impacts. However, biodiesel degrades over time during storage, caused by exposure to light, temperature, oxygen and other sources. To reduce the degradation of biodiesel, antioxidants, usually synthetic, are used. These synthetic antioxidants can, during the burning of biodiesel, generate other impacts to the atmosphere. As a solution to the use of synthetic antioxidants, there are several studies in the literature using natural antioxidants, such as: rosemary, coffee leaves, moringa, mint, among others. In the agro-industry, during the production of malt, there is a pre-treatment of barley (maceration), which generates tons of waste that are normally destined in sanitary landfills, for example, a local industry when producing 100 kg of malt generates 0.9 kg of waste, daily generates 8,000 kg of waste per day. Thus, the main purpose of this work is to reuse the macerated barley waste (RCV) as an antioxidant for biodiesel, applied with mixtures of antioxidants with citric acid and ascorbic acid. The techniques of oxidative stability, spectroscopy in the infrared region, Raman region, thermogravimetry with DSC, elemental composition and high performance liquid chromatography were employed. This agroindustrial residue can be used as an antioxidant for biodiesel, reducing the volume of waste in landfills.